Development of a Novel Framework for the Assessment and Improvement of Climate Adaptation and Mitigation Actions in Europe - Ottaviani Aalmo, Giovanna; Gioli, Beniamino; Rodriguez, Divina Gracia P.; Tuomasjukka, Diana; Liu, Hai-Ying; Pastore, Maria Chiara; Salbitano, Fabio; Bogetoft, Peter; Sæbø, Arne; Konijnendijk, Cecil (Frontiers in Sustainable Cities, 2022)
The greenhouse gases (GHG) emissions in the European Union (EU) are mainly caused by human activity from five sectors—power, industry, transport, buildings, and agriculture. To tackle all these challenges, the EU actions and policies have been encouraging initiatives focusing on a holistic approach but these initiatives are not enough coordinated and connected to reach the much needed impact. To strengthen the important role of regions in climate actions, and stimulate wide stakeholders' engagement including citizens, a conceptual framework for enabling rapid and far-reaching climate actions through multi-sectoral regional adaptation pathways is hereby developed. The target audience for this framework is composed by regional policy makers, developers and fellow scientists. The scale of the framework emphasizes the regional function as an important meeting point and delivery arena for European and national climate strategies and objectives both at urban and rural level. The framework is based on transformative and no-regret measures, prioritizing the Key Community Systems (KCS) that most urgently need to be protected from climate impacts and risks.